Effect of casein phosphopeptide-amorphous calcium phosphate on fluoride release and micro-shear bond strength of resin-modified glass ionomer cement in caries-affected dentin - Jamila Nuwayji Agob; Neven Saad Aref; Essam El Saeid Al-Wakeel (Restorative Dentistry & Endodontics)
ObjectivesThis study was conducted to evaluate fluoride release and the micro-shear bond strength of resin-modified glass ionomer cement (RMGIC) in casein phosphopeptide-amorphous calcium phosphate (CPP-ACP)-remineralized caries-affected dentin (CAD).Materials and MethodsExposed dentin surfaces of 30 human third molar teeth were divided into 2 equal groups for evaluating fluoride release and the micro-shear bond strength of RMGIC to CAD. Each group was subdivided into 3 equal subgroups: 1) control (sound dentin); 2) artificially demineralized dentin (CAD); 3) CPP-ACP remineralized dentin (remineralized CAD). To measure fluoride release, 15 disc-shaped specimens of RMGIC (4 mm in diameter and 2 mm in thickness) were bonded on one flat surface of the dentin discs of each group. Fluoride release was tested using ion chromatography at different intervals; 24 hours, 3, 5, 7 days. RMGIC micro-cylinders were built on the flat dentin surface of the 15 discs, which were prepared according to the assigned group. Micro-shear bond strength was measured after 24 hours water storage. Data were analyzed using 1- and 2-way analysis of variance and the post hoc least significant difference test (α = 0.05).ResultsFluoride detected in solutions (at all intervals) and the micro-shear bond strength of RMGIC bonded to CPP-ACP-remineralized dentin were significantly higher than those bonded to artificial CAD (p < 0.05).ConclusionsDemineralized CAD consumes more fluoride released from RMGIC into the solution for remineralization than CPP-ACP mineralized dentin does. CPP-ACP increases the micro-shear bond strength of RMGIC to CAD.